Inflation Targeting and Inflation Forecasts under Conditions of Increased Uncertainty: Evidence from Poland - Czekaj, Jan; Oleksy, Paweł; Bolisęga, Maciej (Central and Eastern European Economic Review, 2025)
Objective: This paper aims to assess the National Bank of Poland’s efficacy in implementing inflation-targeting monetary policy amidst heightened uncertainty and inflationary pressures during the 2020–2022 period.Research Design & Methods: Standard forecast error metrics (MAE, MAPE, RMSE) are employed to evaluate the accuracy of inflation forecasts by the National Bank of Poland (NBP). Additionally, qualitative analysis of NBP communication is conducted to discern signals or processes that indicate a departure from the pure inflation-targeting regime. Furthermore, outright buy operations of the NBP are scrutinised to ascertain the true purpose of quantitative easing undertaken during 2020–2021 and its alignment with inflation-targeting policy. Finally, both actual and projected inflation rates are examined for potential inconsistencies in the central bank’s responses to ongoing inflationary trends.Findings: Analysis of forecast errors and accuracy metrics reveals a significant deterioration in the quality of inflation projections, rendering them ineffective in guiding monetary policy decisions in extreme times. Moreover, examination of selected actions by the NBP indicates deviations from the strict inflation targeting regime, resulting in inappropriate and untimely decisions to tighten monetary policy.Implications/Recommendations: Discrepancies observed between formal and actual goals of domestic monetary policy, evident in central bank communication, the true purpose of quantitative easing (QE) operations, and the timing or direction of monetary decisions between 2020 and 2022, suggest the need for policymakers to recalibrate or reinforce the legal framework.Contribution: This study extends the current understanding of the effectiveness of monetary policy under strict inflation targeting in a volatile economic environment. Analysing the approach of the National Bank of Poland in 2020–2022, it provides valuable insights into how discrepancies between the formal and actual goals of monetary policy may impact inflation rates.